Scattering of gold nanoparticles in an evanescent waveguide eld - Karlberg, Martin (My University, 2014)
Biomedicine aims at the development of improvement of medical care. One aspect of this aim is the early detection of the onset of disease. In this thesis, single molecule detection by optical waveguides has been used for the detection of low concentration of substances, a method that could be useful for the early discovery of diseases or harmful substances in the body. As such techniques are not yet optimised, this thesis presents a further analyse of such setups. It is of importance to catch sight of the disease as early as possible in order to be able to delay or cure it. Single molecule detection by optical waveguides is a method for detection of low concentrations of substances which could be useful in the early discovery of diseases or harmful substances in your body. The technique is not yet optimised and it is therefore required that it is analysed more into detail before it can be used reliably. The rst part of this thesis explains the theory behind optical waveguides and the formation of modes within them and also the scattering process of nanoparticles situated in their evanescent eld. The second part of the thesis investigates if it is possible to simulate gold nanoparticles in a waveguide's evanescent eld to observe and map how they scatter. COMSOL Multiphysics was used for this type of simulation. The last part explains the experimental e orts made to optimise the method of particle detection using the waveguide platform. The conclusion is that the technique of single molecule detection through scattering on waveguides is a useful method for bio-related applications. It is furthermore concluded that it is possible through scatter measurements to determine the size of di erent particles immobilised on the waveguide surface, if there are known particles of reference. This area of research should be studied further, as there could be a plethora of application areas, chie y within biomedicine.
Keywords: Grundläggande vetenskaper; Nanoteknik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanovetenskap och nanoteknik; Basic Sciences; Nano Technology; Sustainable Development; Innovation & Entrepreneurship; Nanoscience & Nanotechnology